More metaphysician than politician: Pynchon, TINA, and the rhetorical economy of 'The World (This One)'. Issue 3 (16th March 2019) - Chetwynd, Ali
ABSTRACT: This paper examines Thomas Pynchon's fiction as an investigation of the metaphysical preconditions necessary for any concrete political approach to succeed in an era in which capitalism's destruction of possibilities alternative to itself seems like a fait accompli . Such a reading requires a broadened conception of 'economy', taking in affective and rhetorical structures as well as financial ones, all of which hinge on details of Pynchon's metaphysical worldbuilding that recent 'politics first' criticism has downplayed. Pynchon grants existence to many worlds, but makes them all subordinate to our own. How, he asks, could we, in our world and timeline, recuperate the lost or cynically destroyed possibilities of the past such that they can become present again, and operate to improve that world? I use the non-fiction Pynchon published between Gravity's Rainbow (1973) and Vineland (1990) to identify how Mason & Dixon (1997) and Against the Day (2006) frame and answer this question. I then show exactly how the specific metaphysical structures Pynchon generates lead to specific affective dynamics between text and reader that can be understood as economies insofar as they allocate energy to specific political imperatives.